1998
DOI: 10.1128/jcm.36.6.1700-1703.1998
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Enterocolitis Associated with Dual Infection with Enteropathogenic Escherichia coli and Lawsonia intracellularis in Rabbits

Abstract: Both enteropathogenic Escherichia coli (EPEC) and an obligate intracellular bacterium, previously referred to as an intracellular Campylobacter-like organism and now designated Lawsonia intracellularis, have been reported as causes of enterocolitis in rabbits. An outbreak of enterocolitis in a group of rabbits, characterized by an unusually high rate of mortality, was found to be associated with dual infection with EPEC and L. intracellularis. The EPEC strain was found to haveeaeA gene homology but was negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Several studies have noted concurrent infections in animals suffering from PE: spirochetosis in rhesus macaques and Escherichia coli enteropathy in European hamsters and rabbits. Unfortunately, researchers were not able to determine the pathogenesis of these dual infections: if L intracellularis was at the root of the infection and allowed another disease to develop, if a synergism mechanism was at play or if those coinfections were incidental 4 8 18…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have noted concurrent infections in animals suffering from PE: spirochetosis in rhesus macaques and Escherichia coli enteropathy in European hamsters and rabbits. Unfortunately, researchers were not able to determine the pathogenesis of these dual infections: if L intracellularis was at the root of the infection and allowed another disease to develop, if a synergism mechanism was at play or if those coinfections were incidental 4 8 18…”
Section: Discussionmentioning
confidence: 99%
“…Other examples of dual infections with EPEC and another pathogen have also been reported. For example, Schauer et al noted an outbreak of enterocolitis in rabbits due to the combination of rabbit EPEC and an intracellular pathogen, Lawsonia intracellularis (48). In a study of turkeys, Guy et al found that dual infection with an avian EPEC and turkey coronavirus produced a much higher mortality rate than with either microbe singly (30).…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit EPEC is an attaching and effacing E coli strain, where bacterial adherence, via a fimbrial adhesin, results in destruction of the brush border and rearrangement of the enterocyte structure. High levels of Shiga toxin are not expressed by EPEC strains [62]. Transmission is by the fecal-oral route.…”
Section: Coliobacillosismentioning
confidence: 99%
“…Loperamide hydrochloride and fluid rehydration proved successful in the treatment of an E coli outbreak in 22 adult New Zealand white rabbits all fully recovered within 2 weeks [57]. Prognosis is guarded to poor, but is dependent on the strain of E coli, immunocompetence of the animal and presence of synergistic copathogens such as Lawsonia intracellularis (Campylobacter-like organism) or rotavirus [62].…”
Section: Coliobacillosismentioning
confidence: 99%